In silico proteomic and phylogenetic analysis of the outer membrane protein repertoire of gastric Helicobacter species. Issue 1 (December 2018) - Bauwens, Eva; Joosten, Myrthe; Taganna, Joemar; Rossi, Mirko; Debraekeleer, Ayla; Tay, Alfred; Peters, Fanny; Backert, Steffen; Fox, James; Ducatelle, Richard; Remaut, Han; Haesebrouck, Freddy; et al.
Abstract Helicobacter (H .) pylori is an important risk factor for gastric malignancies worldwide. Its outer membrane proteome takes an important role in colonization of the human gastric mucosa. However, in zoonotic non-H .pylori helicobacters (NHPHs) also associated with human gastric disease, the composition of the outer membrane (OM) proteome and its relative contribution to disease remain largely unknown. By means of a comprehensive survey of the diversity and distribution of predicted outer membrane proteins (OMPs) identified in all known gastricHelicobacter species with fully annotated genome sequences, we found genus- and species-specific families known or thought to be implicated in virulence. Hop adhesins, part of theHelicobacter -specific family 13 (Hop, Hor andHom ) were restricted to the gastric speciesH .pylori, H .cetorum andH .acinonychis . Hof proteins (family 33) were putative adhesins with predicted Occ- or MOMP-family like 18-stranded β-barrels. They were found to be widespread amongst all gastricHelicobacter species only sporadically detected in enterohepaticHelicobacter species. These latter are other members within the genusHelicobacter, although ecologically and genetically distinct. LpxR, a lipopolysaccharide remodeling factor, was also detected in all gastricHelicobacter species but lacking as well from the enterohepatic speciesH .cinaedi, H .equorum andH .hepaticus . In conclusion, our systemic survey ofHelicobacter OMPs points to species and infection-site specific members that are interesting candidates for future virulence and colonization studies.